2011
DOI: 10.1007/s11999-011-1904-0
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Apps for Orthopaedic Surgeons

Abstract: Background The use of smartphones and their associated applications (apps) provides new opportunities for physicians, and specifically orthopaedic surgeons, to integrate technology into clinical practice. Purpose The purpose of this study was twofold: to review all apps specifically created for orthopaedic surgeons and to survey orthopaedic residents and surgeons in the United States to characterize the need for novel apps. Methods The five most popular smartphone app stores were searched for orthopaedic-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(138 citation statements)
references
References 11 publications
(16 reference statements)
2
134
0
1
Order By: Relevance
“…In comparison to orthopaedic apps, with 61 apps in total and 17 apps with over ten reviews 3 , there were far fewer neurosurgical apps available. Given the number of ratings were given for the neurosurgical apps, these were likely also less popular.…”
Section: Neurology Psychiatry Osces)mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to orthopaedic apps, with 61 apps in total and 17 apps with over ten reviews 3 , there were far fewer neurosurgical apps available. Given the number of ratings were given for the neurosurgical apps, these were likely also less popular.…”
Section: Neurology Psychiatry Osces)mentioning
confidence: 99%
“…It has been used for education and clinical decisions for orthopaedic surgeons 3 , paging doctors in hospitals, 4 and assessing wounds. 5 There has also been clinical use of consumer technology in neurosurgery, with video conferencing shown to be effective in aiding consultations 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Although Franko reported that there are few specific highly ranked orthopaedic apps available [5], we think there are numerous applications that may be used to meet the needs of an orthopaedic trainee.…”
Section: To the Editormentioning
confidence: 99%
“…We read with interest the article ''Smartphone apps for Orthopaedic Surgeons'' by Franko in the July 2011 issue of CORR 1 [5]. We welcome any technology that would augment surgical training and lead to prudent use of time and resources, and even more so in the UK health system.…”
Section: To the Editormentioning
confidence: 99%
“…In fact, since the initial publication of ''Smartphone apps for Orthopaedic Surgeons'' in July 2011 [3], much has changed in the realm of available orthopaedic apps. A followup study specifically examining iPad apps [4] and another review of orthopaedic apps [1] were published.…”
mentioning
confidence: 99%